2015 IEEE 27th International Symposium on Power Semiconductor Devices &Amp; IC's (ISPSD) 2015
DOI: 10.1109/ispsd.2015.7123397
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of single-event burnout for super junction MOSFET

Abstract: Single-Event Burnout (SEB) is one of the catastrophic failure effects that could cause destruction of a MOSFET. In the present work, we experimentally obtained the dependence of SEB tolerance of Super-junction (SJ) MOSFET on temperature and studied the mechanism of the dependence of SEB failure rate on temperature by simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…An empirical formula reported in [15], valid for Si devices, predicts an exponential decreasing of the failure rate with increasing temperature. This trend was observed in [12] for Super-Junction Si MOSFET. The exponential dependence of the FIT on the temperature observed in Si devices does not hold for SiC power MOSFETs, which showed a weaker temperature dependence, as observed in [14].…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…An empirical formula reported in [15], valid for Si devices, predicts an exponential decreasing of the failure rate with increasing temperature. This trend was observed in [12] for Super-Junction Si MOSFET. The exponential dependence of the FIT on the temperature observed in Si devices does not hold for SiC power MOSFETs, which showed a weaker temperature dependence, as observed in [14].…”
Section: Introductionsupporting
confidence: 69%
“…Concerning the temperature dependence at fixed drain voltage of the FIT values of the SiC power MOSFETs, the results of our investigation confirmed the lower temperature dependence of the silicon power MOSFETs and showed that the FIT-temperature curves depend on the SiC device and its bias condition. Some physical mechanisms governing the temperature dependence of the SEB failures have been proposed in [12] for Si MOSFETs and in [14] for SiC MOSFETs. For silicon devices, the SEB mechanism is due to the parasitic bipolar transistor turn-on due to the dense electron-hole plasma produced by an ion which traverses the depletion region of the n-channel MOSFET [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikeda et al [100] later showed experimentally that an SJ offered no improvement to SEB tolerance over a VDMOSFET. Further simulation and experimental studies on Si SJ MOSFETs showed there was no inherent advantage in SEE tolerance [101][102][103][104][105]. More recently, it has been demonstrated that SJ theory can be effective for SiC power MOSFETs [106], and the first SiC SJ MOSFET was demonstrated in [107] at the 2016 ESCRM.…”
Section: Baseline Superjunction Mosfet Seb Performancementioning
confidence: 99%